The Impacts of Non-linear Oil Price Shocks on Saudi Savinginvestment Behavior: An Empirical Investigation - Algaeed, Abdulaziz Hamad (International Journal of Economics and Financial Issues, 2017)
The purpose of this paper is to analyze theoretically and empirically the effects of a non-linear oil price shocks on Saudi investment-saving behavior for the period of 1985-2015, using structural vector autoregressive (SVAR) approach. The oil price shock is calculated as SOPI, employing GARCH (1,1). Johansen’s testing procedure result asserts the existence of stable long-run relationship between private saving investment (PI), oil price shock (OIL shock), government expenditure (GOEX) and per-capita income (PERCAPITA). The findings confirm that the oil price shocks affect positively (+) private investment. The sign is as expected and significant. Moreover, capital investment takes time to absorb the shock. Nonetheless, per-capita income as a proxy for aggregate demand had the right sign and statistically significant. Government expenditure had the positive sign reflecting the crowd-in effects. Although, Emmanuel, et al. (2014), found negative impacts of oil price shocks on private investment, our results should differ in sign because this analysis is forwarded towards an oil-exporting country. Keywords: Investment, Saudi Arabia, A nonlinear oil price shocks, and SVAR. JEL Classifications: C51; E22; Q43